2022
DOI: 10.1073/pnas.2115082119
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a dual-action small molecule that improves neuropathological features of Alzheimer’s disease mice

Abstract: Alzheimer’s disease (AD) is characterized by complex, multifactorial neuropathology, suggesting that small molecules targeting multiple neuropathological factors are likely required to successfully impact clinical progression. Acid sphingomyelinase (ASM) activation has been recognized as an important contributor to these neuropathological features in AD, leading to the concept of using ASM inhibitors for the treatment of this disorder. Here we report the identification of KARI 201, a direct ASM inhibitor evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…KARI201 normalizes ASM activity without affecting protein level of ASM or mRNA transcript level of SMPD1 , the gene coding for ASM. However, this drug is associated with significantly reduced Aβ levels and improved autophagic and phagocytic microglial activity [ 101 ]. ASM inhibition also encourages OL maturation and/or survival [ 102 ].…”
Section: Exploring Other Targets Implicated In Both Myelin Repair and Admentioning
confidence: 99%
See 1 more Smart Citation
“…KARI201 normalizes ASM activity without affecting protein level of ASM or mRNA transcript level of SMPD1 , the gene coding for ASM. However, this drug is associated with significantly reduced Aβ levels and improved autophagic and phagocytic microglial activity [ 101 ]. ASM inhibition also encourages OL maturation and/or survival [ 102 ].…”
Section: Exploring Other Targets Implicated In Both Myelin Repair and Admentioning
confidence: 99%
“…ASM inhibition also encourages OL maturation and/or survival [ 102 ]. KARI201 is also found to have a dual action as a ghrelin receptor agonist; agonism of this receptor is known to promote hippocampal synaptic density, plasticity, and neurogenesis in the context of AD [ 101 ].…”
Section: Exploring Other Targets Implicated In Both Myelin Repair and Admentioning
confidence: 99%
“…To date, different types of ASM inhibitors have been reported, including natural, non-natural, physiological, and functional inhibitors. Besides, several research groups have reported some direct inhibitors of ASM including KARI 201 [ 93 ], ARC39 [ 94 ], AD2765 [ 95 ], and SMA-7 [ 96 ]. In addition, α-mangostin [ 97 ], cowanol, and cowanin [ 85 ] are natural ASM inhibitors, while various physiological inhibitors, including L-αphosphatidyl-D-myoinositol-3,5-biphosphate [ 98 ] and phosphatidyl-myo-inositol-3,4,5-triphosphate [ 99 ] also inhibits ASM.…”
Section: Therapeutics Targeting Ceramide Biosynthesismentioning
confidence: 99%
“…However, these inhibitors lack specificity, have off-target effects, and have unclear mechanisms of therapeutic action in neurodegenerative diseases. Based on this, a new small compound was recently identified as a selective and direct ASM inhibitor without off-target effects ( 31 ). This ASM inhibitor is significantly effective in improving neuroinflammation, autophagy dysfunction, synapse loss, neuronal survival, and activity in neurodegenerative diseases ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, a new small compound was recently identified as a selective and direct ASM inhibitor without off-target effects ( 31 ). This ASM inhibitor is significantly effective in improving neuroinflammation, autophagy dysfunction, synapse loss, neuronal survival, and activity in neurodegenerative diseases ( 31 ). Moreover, this inhibitor exhibits excellent bioavailability, central nervous system distribution, and microsomal stability.…”
Section: Discussionmentioning
confidence: 99%